PENGEMBANGAN MATERI KOMUNIKASI INTERPERSONAL - Yanti, Riri Ramada; Umari, Tri; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to develop interpersonal communication materials class X SLTA/MA equals, and a description of its feasibility in terms of aspects of clarity, systematics, image support, freshness, completeness of the material, and support for video or games. Type of research is the development of data analysis techniques using data validity. The source of the data obtained from the supervisor 1, supervisor 2, two teachers BK, and 26 students of class X Telkom SMK Telkom Pekanbaru. The results showed that the material has been developed interpersonal communication with all aspects of yhe quality of the material is very good. So that the material is fit for use by teachers guidance and counseling in schools.Key Words: Materials Counseling, Interpersonal Communication